Excitability-Independent Memory Allocation for Repeated Event - Cho, Hye-Yeon; Lee, Han-Sol; Jeong, Yire; Han, Junho; Yoo, Miran; Han, Jin-Hee (Frontiers in Behavioral Neuroscience, 2022)
How memory is organized in cell ensembles when an event is repeated is not well understood. Recently, we found that retraining 24 h after initial fear conditioning (FC) event induces turnover of neurons in the lateral amygdala (LA) that encode fear memory. Excitability-dependent competition between eligible neurons has been suggested as a rule that governs memory allocation. However, it remains undetermined whether excitability is also involved in allocation of repeated event. By increasing excitability in a subset of neurons in the LA before FC, we confirmed that these neurons preferentially participated in encoding fear memory as previously reported. These neurons, however, became unnecessary for memory recall after retraining 24 h following initial FC. Consistently, the initial memory-encoding neurons became less likely to be reactivated during recall. This reorganization in cell ensembles, however, was not induced and memory was co-allocated when retraining occurred 6 h after initial FC. In 24-h retraining condition, artificially increasing excitability right before retraining failed to drive memory co-allocation. These results suggest a distinct memory allocation mechanism for repeated events distantly separated in time.